Playing the odds: prioritizing human rabies biologics in limited supply scenarios (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Limitations in the availability and access to human rabies biologics in enzootic regions result in most rabies deaths in the developing world. Efforts to supply modern rabies vaccines and immune globulin (RIG) have improved availability, but cost and the lack of structured programs in many countries remain major obstacles to providing optimal care. Proposed policies to provide rabies post-exposure prophylaxis (PEP) at no cost to the patient through government programs are challenged by the limited supply of rabies biologics that providers are able to obtain. In many cases, the demand for biologics exceeds the limited supplies and national rabies programs are therefore forced to ration, resulting in delays or complete failures in provision of adequate PEP. Optimal PEP involves the use of rabies immune globulin and vaccine. While WHO recommendations for PEP are comprehensive, those recommendations offer no guidance on management of rabies exposures when there are limited supplies of biologics in the country nor if there is only vaccine available but no RIG. Complex operationalization issues, such as to how to approach prioritization when both nervous tissue and modern vaccines coexist in a country, or how to optimally integrate private distribution of rabies biologics, are not part of the WHO guidance documents. We present a proposal on how to develop recommendations and guidelines to deal with these scenarios accounting for local rabies epidemiology, patient age and body size, delays after exposure, and cultural and social issues. Several Old and New World country cases are presented to highlight how these challenging circumstances might be managed and overcome.